Effects of Electronic Devices and Internet Addiction on Sleep and Academic Performance Among Female Egyptian and Saudi Nursing Students: A Comparative Study - Amal Ahmed Elbilgahy; Rasha Kamal Sweelam; Fatma Abdou Eltaib; Hanaa E. Bayomy; Shereen Ahmed Elwasefy (SAGE Publishing, 2021)
Introduction The widespread availability of Internet access and increasing rate of electronic device usage has helped enlighten the world community through copious applications, information resources, and other benefits. However, both the lack of controlled behavior and excessive Internet usage have resulted in a variety of difficulties that can hinder user achievement in many areas. Objectives This study investigated the prevalence of Internet and electronic device addiction among Egyptian and Saudi nursing students, with the aim of identifying any effects on sleep and academic performance. Methods A cross-sectional comparative research design was employed among a systematic random sample comprised of 920 Egyptian and Saudi female nursing students. All participants completed the Young-Internet Addiction Test (IAT), Mobile Phone Involvement Questionnaire (MPIQ), and Epworth Sleepiness Scale (ESS). Results Severe Internet Addiction (IA) detected in 42.69% and 10.31% of Saudi and Egyptian participants, respectively. However, Saudi participants were more likely to report high rates of mobile phone usage ( P  < 0.001), while Egyptian participants tended to score higher on the ESS (17.47 ± 3.99 vs. 16.8 ± 3.83; P  = 0.024). For all participants, IAT and MPIQ scores were correlated with ESS results, while IA was specifically associated with poor academic performance. Finally, MPIQ scores were inversely correlated with academic performance for Saudi participants. Conclusion Smartphone and Internet addiction were notable problems for the Egyptian and Saudi nursing students investigated in this study. Importantly, these conditions adversely affect academic performance and other activity engagement in addition to inducing excessive daytime sleepiness.